Structural and Semantic Analysis of the Auxiliary Verb ~You (da) in Japanese Sentences - Nani Sunarni; Herawati, Isye (Chi e Journal of Japanese Learning and Teaching, 2025)
This study investigates the structure and meaning of the auxiliary verb ~you (da) in Japanese sentences. Data were collected from the Books Bunpou ga Yowai Anata e and Manabo! Nihongo Shou (Chuukyuu) and self-constructed sentences reviewed by native speaker linguists. Using a qualitative descriptive approach, 29 instances of ~you (da) were analyzed and categorized into three meanings: assumption based on observation (15 cases), similarity or equality (6 cases), and comparison or analogy (8 cases). The findings reveal that ~you (da) structurally attach to verbs, adjectives, and nouns in their base forms, functioning as predicates. Semantically, it conveys two core meanings: (1) assumption based on observation or perceived conditions and (2) expressions of similarity, resemblance, or analogy. The latter meaning is further divided into reiji (例示), which provides examples, and Hikyou (比況), which expresses similarity through comparison. These meanings are realized through patterns such as [V+you ni V], [N+ no you ni + V/Adj], and [N + no you da]. This study contributes to Japanese grammar research by clarifying the syntactic and semantic roles of ~you (da). The analysis follows the sentence study approach and the matching method, examining linguistic elements based on their referential meanings. By offering a structured analysis of ~you (da), this study enhances the understanding of its usage and provides insights for learners and educators in Japanese language studies.